2004
DOI: 10.1016/j.jacc.2004.01.042
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and prognosis in patients with left ventricular systolic dysfunction after a myocardial infarction

Abstract: In patients with LV dysfunction after an MI, light-to-moderate alcohol intake either at baseline or following MI did not alter the risk for the development of HF requiring hospitalization or an open-label angiotensin-converting enzyme inhibitor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…7 Older patients with HF differ from younger patients in that a higher proportion of older patients with HF have HF with preserved ejection fraction. 15 These patients are less likely to have CHD and more likely to have hypertension and atrial fibrillation. 16 A high proportion of men without a history of a doctor diagnosis of an MI in this study who developed HF did not develop an MI before developing HF (85%), which would explain the difference in findings between this and the younger US cohorts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Older patients with HF differ from younger patients in that a higher proportion of older patients with HF have HF with preserved ejection fraction. 15 These patients are less likely to have CHD and more likely to have hypertension and atrial fibrillation. 16 A high proportion of men without a history of a doctor diagnosis of an MI in this study who developed HF did not develop an MI before developing HF (85%), which would explain the difference in findings between this and the younger US cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…11 This suggests that the lower risk of HF associated with light-to-moderate drinking may be mediated through beneficial effects of alcohol on coronary heart disease (CHD). 11 However, few studies have examined the association between alcohol drinking and risk of HF in older adults, in whom the occurrence of HF with preserved ejection fraction is more common than HF with reduced ejection fraction 15 and in whom HF is less likely to be associated with CHD. 16 Moreover, in most population-based cohort studies which have examined the association between alcohol consumption and HF risk, heavier drinking (>3 drinks/day) is underrepresented and the level of alcohol intake which is associated with increased HF risk is less certain although prospective population-based studies have suggested that the risk of developing atrial fibrillation, a major risk factor for HF, increases significantly with 5 or more drinks/ day 17 and at an even lower threshold (>3 drinks/day) in those with cardiovascular (CV) disease (CVD).…”
Section: Key Messagesmentioning
confidence: 99%
“…10 In 2231 patients from SAVE trial, with an LVEF <40% after MI, light-to-moderate alcohol intake did not alter the risk of hospitalization for HF. 8 In 449 male US physicians with HF a J-shaped relation between alcohol intake and mortality was reported, so the risk was significantly lower only in those drinking 1 to 2 glasses per day. 14 In contrast, the study on 1332 Italian subjects aged ≥65 years found that alcohol consumption was associated with a 21% lower risk of death in subjects without HF, but a 29% higher risk of death in patients with chronic HF.…”
Section: Wine Consumption and Clinical Outcomesmentioning
confidence: 99%
“…However, while alcohol drinking is inversely related to the risk of CAD-associated HF, heavy (but not light/ moderate) drinkers have a raised risk of non-CAD associated HF. 43 Further reports 44,45 argue against light drinking as a mechanism to increase the risk of HF as well.…”
Section: Nonoxidative Metabolism Of Alcohol and Myocyte Damagementioning
confidence: 99%